Multi-material cellular structured orthopedic implants design: In vitro and bio-tribological performance. (July 2022) - Costa, M.M.; Lima, R.; Alves, N.; Silva, N.A.; Gasik, M.; Silva, F.S.; Bartolomeu, F.; Miranda, G.
Abstract: In this study, Selective Laser Melting (SLM) was used to produce mono-material Ti64Al4V- and NiTi-cubic cellular structures with an open-cell size and wall thickness of 500 μm and 100 μm, respectively. Bioactive beta-tricalcium phosphate (βTCP) and polymer poly-ether-ether ketone (PEEK) were used to fill the produced structures open-cells, thus creating multi-material components. These structures were characterized in vitro in terms of cell viability, adhesion, differentiation and mineralization. Also, bio-tribological experiments were performed against bovine plate to mimic the moment of implant insertion. Results revealed that metabolic activity and mineralization were improved on SLM mono-material groups, when compared to the control group. All cell metrics were improved with the addition of PEEK, conversely to βTCP where no significant differences were found. These results suggest that the proposed solutions can be used to improve implants performance. Graphical abstract: Image 1 Highlights: Ti- and NiTi-based structures were produced by SLM and pressure-assisted methods. In vitro and bio-tribological tests were made and benchmarked against Ti64 SLA. Ti and NiTi structures showed improved biological response when compared with SLA. PEEK-filled structures show positive cellular response, conversely to βTCP. These solutions ensure adequate in vitro response, while keeping primary stability.